KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM MENANGANI SENGKETA ANTARA PT. SINAR MENARA DELI DENGAN SARI ALAMSYAH - Samuel Samuel; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2019)
In principle, the resolution of consumer disputes can be pursued peacefully. through an alternative mediation dispute resolution. In Law Number 8 of 1999 concerning Consumer Protection and Regulation of the Minister of Trade of the Republic of Indonesia Number 6 / M-DAG / PER / 2017 concerning the Consumer Dispute Settlement Body does not impose limits on the authority of BPSK in handling and adjudicating a consumer dispute. However, in reality many times the decisions of the Consumer Dispute Settlement Body (BPSK) are submitted to the district court and stated that BPSK is not authorized to handle such disputes. How is the authority of the Consumer Dispute Resolution Board in handling disputes between PT. Sinar Menara Deli and Sari Alamsyah are the issues discussed. The method used in this research is descriptive normative legal research, using secondary data and primary data as supporting data with the law approach. The results of the study illustrate that BPSK is not authorized to handle disputes between PT. Sinar Menara Deli with Sari Alamsyah, because the business actors in this dispute have submitted a refusal to be resolved through BPSK and not achieving the requirements for consumer disputes. It is recommended that BPSK members pay more attention to the provisions in the Consumer Protection Act and other regulations concerning the Consumer Dispute Settlement Body.